The Burden of Leprosy Reaction in the Post-Elimination Era: A Study from Gresik City, Indonesia - Kinanti, Hapsari; Kurniati; Faidati, Wind (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2024)
Background: The attention of leprosy management has shifted to reduce the burden of leprosy complications, including leprosy reactions. Leprosy reaction is the predominant cause of nerve impairment that leads to disability and lowers the quality of life of the affected. Purpose: The aim of this study was to provide primary data about leprosy reaction epidemiology, risk factor, and outcomes in the post-elimination era.  Methods: A cross-sectional study was held in a general hospital in Gresik City, Indonesia, to give clinical demography, risk factors, and outcomes of leprosy reaction. Result: New leprosy reaction cases remain detected each year. There were 57 (58.8%) out of 97 leprosy patients who had a reactional episode. The incidence of leprosy reactions has been increasing in the last three years. The multibacillary (MB) group and type 2 reactions dominated leprosy reactions, which mostly occurred in the young adult population. Some of the leprosy reaction patients had developed a complication due to prolonged steroid usage. Conclusion: Leprosy cases in a young population with a high risk of developing reaction episodes need collaboration in the management to prevent deformity in youth.